Genome-wide analysis of pediatric-type follicular lymphoma reveals low genetic complexity and recurrent alterations of TNFRSF14 gene - Schmidt, Janine; Endris, Volker; Penzel, Roland (Blood, 2016)
Pediatric-type follicular lymphoma (PTFL) is a variant of follicular lymphoma (FL) with distinctive clinicopathological features. Patients are predominantly young males presenting with localized lymphadenopathy; the tumor shows high-grade cytology and lacks both BCL2 expression and t(14;18) translocation. The genetic alterations involved in the pathogenesis of PTFL are unknown. Therefore, 42 PTFL (40 males and 2 females; mean age, 16 years; range, 5-31) were genetically characterized. For comparison, 11 cases of conventional t(14:18)− FL in adults were investigated. Morphologically, PTFL cases had follicular growth pattern without diffuse areas and characteristic immunophenotype. All cases showed monoclonal immunoglobulin (IG) rearrangement. PTFL displays low genomic complexity when compared with t(14;18)− FL (mean, 0.77 vs 9 copy number alterations per case; P < .001). Both groups presented 1p36 alterations including TNFRSF14, but copy-number neutral loss of heterozygosity (CNN-LOH) of this locus was more frequently observed in PTFL (40% vs 9%; P = .075). TNFRSF14 was the most frequently affected gene in PTFL (21 mutations and 2 deletions), identified in 54% of cases, followed by KMT2D mutations in 16%. Other histone-modifying genes were rarely affected. In contrast, t(14;18)− FL displayed a mutational profile similar to t(14;18)+ FL. In 8 PTFL cases (19%), no genetic alterations were identified beyond IG monoclonal rearrangement. The genetic landscape of PTFL suggests that TNFRSF14 mutations accompanied by CNN-LOH of the 1p36 locus in over 70% of mutated cases, as additional selection mechanism, might play a key role in the pathogenesis of this disease. The genetic profiles of PTFL and t(14;18)− FL in adults indicate that these are two different disorders.